Pneumonia Classification Based on GLCM Features Extraction using K-Nearest Neighbor - Suharyana Suharyana; Fuad Anwar; Armylia Chandra Dewi; Mohtar Yunianto; Umi Salamah; Rifai Chai (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Pneumonia has been detected using Machine learning. The stages in this study began with preprocessing in 4 stages: resizing, cropping, filtering using a high pass filter, and Adaptive Histogram Equalization. The feature extraction process continued with 22 Gray Level Co-occurrence Matrix (GLCM) features and classification using K-Nearest Neighbor (KNN). The image used was 150 data sets for training on the classification of 3 classes with a ratio of 50:50:50 while training on two classes was 50 bacterial pneumonia and 50 viral pneumonia. The most optimal training data accuracy results were obtained using the angle direction on the GLCM, namely 135o with the KNN classification (k = 3). For the classification of two classes Using 40 data sets, an accuracy of 91% was obtained, while testing for three classes with 60 data sets was 83.3%.